2020
DOI: 10.1002/csc2.20146
|View full text |Cite
|
Sign up to set email alerts
|

Managing forage and turf‐type bahiagrass for seed production

Abstract: Bahiagrass (Paspalum notatum Flüggé) is the most extensively cultivated perennial warm-season grass in the southeastern United States for pasture, utility turf, cover cropping, and soil stabilization. The University of Florida Institute of Food and Agricultural Sciences bahiagrass breeding program has recently selected several improved forage-and dwarf-turf-type tetraploid breeding lines. However, seed production and seed quality quantification is needed before proposing any of these lines for cultivar release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(83 reference statements)
1
6
1
Order By: Relevance
“…Sward age has a strong effect on Paspalum SY, and greater seed production has been observed in the first year of production. Previous research on P. plicatulum (Chadhokar & Humphreys, 1973) and P. notatum (Rios et al., 2020) showed most of the response variables, except seed weight, exhibited significantly better performance during the first year of production. Therefore, productive behavior over time requires more research.…”
Section: Discussionmentioning
confidence: 82%
“…Sward age has a strong effect on Paspalum SY, and greater seed production has been observed in the first year of production. Previous research on P. plicatulum (Chadhokar & Humphreys, 1973) and P. notatum (Rios et al., 2020) showed most of the response variables, except seed weight, exhibited significantly better performance during the first year of production. Therefore, productive behavior over time requires more research.…”
Section: Discussionmentioning
confidence: 82%
“…Considering Urochloa , the mean number of filled seeds per individual (%) for eight different hybrids was 4.6% (Ragalzi et al., 2021). For bahiagrass ( Paspalum notatum Flüggé) genotypes, GP ranged from 5.1% to 39.3% (Rios et al., 2020). The percentage of filled grains is also one of the main factors that affect rice yield (Yoshida, 1981).…”
Section: Resultsmentioning
confidence: 99%
“…DTF was the only trait that decreased in Year 2 (Figure 3), which may be an indication that a greater number of days for flowering leads to a decrease in seed production. One of the factors that affect productivity and seed quality in Paspalum notatum is the prolonged flowering period (Rios et al., 2020). In forage grasses, the components of seed production are determined from vegetative development to the stages of reproductive development, highlighting the number of inflorescences and the number of flowers per inflorescence (Lopes & Franke, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…produced a higher seed set during the first year of seed production. Adjei, Mislevy, and Chason (1992) and Gates and Burton (1998) found a year effect and interaction with other factors on the seed yield of diploid bahiagrass, and Rios et al (2020) found that for bahiagrass, most of the response variables, except seed weight, exhibited significantly better performance during the first year of production. These contrasting results, observed by different authors and in this study, indicate that observed variations in seed yield in the first year of cultivation are more strongly influenced by climatic conditions than factors related to pasture age.…”
Section: Discussionmentioning
confidence: 97%